Pengaruh Lingkungan Kerja dan Motivasi terhadap Kepuasan Kerja Serta Dampaknya pada Kinerja Karyawan PT. Sinarmas Multifinance Cabang Jambi - Wahyuri, Putra; MS, M. Zahari; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe the work environment, motivation, job satisfaction and performance of PT. Sinarmas Multifiance Jambi Branch and to analyze the influence of work environment and motivation partially and simultaneously directly and indirectly on job satisfaction and employee performance, as well as to analyze job satisfaction on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely work environment, motivation, job satisfaction and performance. In addition, the author is also looking for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study is employees of Sinarmas Multifinance Jambi Branch which amounts to 61 employees with conditions in 2022. The data analysis technique used in this study is through path analysis followed by hypothesis testing through F test (Simultaneous) and t test (Partial). From the path analysis testing conducted, it was found that the work environment and work motivation affected job satisfaction by 46.28% while the rest were influenced by other variants. Work environment and motivation affect 43.14% of employee performance at PT. Sinarmas Multifinance Jambi Branch. This study concludes the work environment, motivation, job satisfaction and employee performance are in good and high condition. In addition, the work environment and motivation partially and simultaneously have a positive and significant influence on job satisfaction and employee performance at PT. Sinarmas Multifinance Jambi Branch. Similarly, job satisfaction has a positive and significant influence on employee performance.